A rentabilidade do cacau de S. Tomé e Príncipe - hipóteses de explicação - Santos, Maciel Morais (Africana Studia, 2020)
Belween lhe 1880's anel 1970's, S. Tomé e Príncipe cocoa growing developped through lhe import of forced labour. whose high costs are generally seen as lhe major canse of the cycle's end. Based on lhe few available statistical data, it is possible to argue that the labour cosls variations were not lhe main determinants of the agricultura! profits. Besicles, some data seem to confirm that the maintenance of slavery was a competi tive advantage, al least in the intensive capital exploitations of S. Tomé.